2015
DOI: 10.1016/j.emj.2015.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Appropriate persistence in a project: The case of the Wine Culture and Tourism Centre in Bordeaux

Abstract: Some authors view persistence as a negative attribute linked to the escalation of commitment, while others argue that perseverance is crucial to innovation. This paper seeks to explore the conditions in which persistence can be considered an appropriate strategy in the development of a project. To this end, we performed a qualitative and longitudinal study on the plan to open a Wine Culture and Tourism Centre in Bordeaux. The idea was first put forward in 1995. After experiencing a number of failures, the cent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 62 publications
(142 reference statements)
0
6
0
Order By: Relevance
“…The supply chain in collaboration has occasionally also missed festivals and events as the cornerstone of bringing communities together using long existing beliefs and values (see Clifton et al, 2012). Special relationships over projects have triumphed where influential stakeholders can rise to support activity (Bordeaux wine centre, Cusin & Passebois-Ducros, 2015). A commitment to growing skills and a destination's capacity to improve business opportunities through regeneration was also evident in a further Scottish example (McCarthy & Doyle, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The supply chain in collaboration has occasionally also missed festivals and events as the cornerstone of bringing communities together using long existing beliefs and values (see Clifton et al, 2012). Special relationships over projects have triumphed where influential stakeholders can rise to support activity (Bordeaux wine centre, Cusin & Passebois-Ducros, 2015). A commitment to growing skills and a destination's capacity to improve business opportunities through regeneration was also evident in a further Scottish example (McCarthy & Doyle, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the study seeks to address several knowledge gaps identified in contemporary research. One major gap relates to micro and small firms' involvement in innovative practices (e.g., Doloreux et al, 2013;Forsman and Rantanen, 2011), while a second is the lack of research on innovative practices in traditional industries (Cusin and Passebois-Ducros, 2015). The country choice for this study is mainly based on Italy's history, tradition, and significance as a wine producing, exporting, and consuming country.…”
Section: Methodsmentioning
confidence: 99%
“…Mirroring the limited body of research, studies focusing on micro and small firm innovation in historic/traditional European industries have been scant, including in the wine industry. More generally, Cusin and Passebois-Ducros (2015) explain that "… no research to date has focused on innovative projects in traditional and conservative sectors with a strong historical legacy, such as the wine industry in the city of Bordeaux." (p. 342).…”
Section: Introductionmentioning
confidence: 99%
“…In order to study in detail the ability of wineries towards orientation purchasing of their clients, today winemakers want to include in the circle of innovations an increasing number of green or eco-innovations. Despite the growing interest in this topic, the scientific research is relatively limited, mainly due to the consideration related to scarce winemaking resources and to the traditional managerial approach in the sector, mainly at national level (Cusin and Passebois-Ducros, 2015). However, in recent years the logic of studying innovations in winemaking has considered possible correlations between consumer preferences for wine and the adoption of eco-certification, bottle recycling, reuse of washing water, emission monitoring or other environmentally friendly actions (Calle et al, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%